Особенности контактной деструкции полимерных инструментальных материалов, содержащих композиционный наполнитель на основе монтмориллонита - Черненко, А.Н.; Пащенко, Е.А.; Лажевская, О.В. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2009)
Degradation of polymer binder of abrasive composites containing synthetic composite filler on the basis of aromatic polytriazine and montmorillonite has been studied. Correlation between activity of the gas products evolved by composite in a processing zone and operational functionality of the tool is shown.